PENGARUH KONSERVATISME AKUNTANSI TERHADAP NILAI PERUSAHAAN: GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Purwanti, Rizky (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is: (a) to test the influence among accounting conservatisms to the companyâs value; (b) to test whether managerial ownership modernize the influence among accounting conservatisms to the companyâs value; (c) to test whether the numbers of independent commissioners moderating the influence of accounting to the companyâs value. The research objects are manufacturing companies which are listed in the Indonesia Stock Exchange during observation periods from 2009 to 2011. The researchâs source of data is secondary data in from of manufacturing companiesâ financial statements which are published by the Indonesia Stock Exchange in website http://www.idx.co.id/ as well as stock data at Indonesia Capital Market Directory (ICMD). Samples collection is carried out by using purposive sampling method. The numbers of samples which have been chosen in this research are 76 companies. The multiple linier regressions analysis is used as the analysis technique. The result of research shows evidences that: (a) accounting conservatisms has positive influence to the companyâs value; (b) managerial ownership moderating the influence among accounting conservatisms to the companyâs value; (c) the number of independent commissioners moderating the influence among accounting conservatisms to the companyâs value.Keywords: accounting conservatism, Managerial Ownership, Independent Commissioner and the value of the company.